Chlorhexidine adoption in Nigeria - Palamountain, Kara; Calkins, Tim (London : Kellogg School of Management, 2017)
It is January 2017, and Nikki Tyler, market access advisor at the U.S. Agency for International Development's Center for Accelerating Innovation and Impact, must recommend an actionable strategy for how to use the $10 million contributed by global donors and foundations to scale up the use of chlorhexidine in Nigeria. It was clear that chlorhexidine, a substance applied to newborns' umbilical cord stumps to prevent infection, could reduce infant mortality significantly. However, changing behavior would be an enormous challenge. This case gives students an appreciation for the importance and complexity of global health issues, along with an understanding of key analytic techniques for approaching a complex market situation. Students quickly learn that there are no easy answers to encouraging chlorhexidine's greater use. To develop a plan, it is essential to complete detailed analyses, study insights and motivations, and ultimately compare different possible solutions, considering efficiency and efficacy.
Originally Published InPalamountain, K., & Calkins, T. (2017). Chlorhexidine adoption in Nigeria. 5-217-255. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Tyler, Nikki; United States. -- Agency for International Development. -- Center for Accelerating Innovation and Impact; Drug accessibility -- Social spects -- Nigera -- Case studies; Health attitudes -- Social aspects -- Nigeria -- Case studies; Patient compliance -- Social aspects -- Nigeria -- Case studies; Chlorhexidine -- Therapeutic use -- Nigeria; Medicine -- International cooperation -- Case studies